IL-10 constrains sphingolipid metabolism via fatty acid desaturation to limit inflammation - York, Autumn G; Skadow, Mathias H; Qu, Rihao; Oh, Joonseok; Mowel, Walter K; Brewer, J Richard; Kaffe, Eleanna; Williams, Kevin J; Kluger, Yuval; Crawford, Jason M; Smale, Stephen T; Bensinger, Steven J; et al. (bioRxiv, 2023)
Unchecked chronic inflammation is the underlying cause of many diseases, ranging from inflammatory bowel disease to obesity and neurodegeneration. Given the deleterious nature of unregulated inflammation, it is not surprising that cells have acquired a diverse arsenal of tactics to limit inflammation. IL-10 is a key anti-inflammatory cytokine that can limit immune cell activation and cytokine production in innate immune cell types; however, the exact mechanism by which IL-10 signaling subdues inflammation remains unclear. Here, we find that IL-10 signaling constrains sphingolipid metabolism. Specifically, we find increased saturated very long chain (VLC) ceramides are critical for the heightened inflammatory gene expression that is a hallmark of IL-10-deficient macrophages. Genetic deletion of CerS2, the enzyme responsible for VLC ceramide production, limited exacerbated inflammatory gene expression associated with IL-10 deficiency both and , indicating that "metabolic correction" is able to reduce inflammation in the absence of IL-10. Surprisingly, accumulation of saturated VLC ceramides was regulated by flux through the mono-unsaturated fatty acid (MUFA) synthesis pathway, where addition of exogenous MUFAs could limit both saturated VLC ceramide production and inflammatory gene expression in the absence of IL-10 signaling. Together, these studies mechanistically define how IL-10 signaling manipulates fatty acid metabolism as part of its molecular anti-inflammatory strategy and could lead to novel and inexpensive approaches to regulate aberrant inflammation.